Multiview as a reflective framework: enabling reflection, transforming practice. (2013) - Green, Gill; Hagan, David; Roberts, David Caton
This paper seeks to offer a methodology for practitioners to encourage the development of meaningful reflection. Such reflection on practical values and theories, which inform everyday actions are a source of continuous learning and define professional practice. This reflection draws on two case studies of the development of separate information systems. The first a case study focused on the design and implementation of an information system that offered a solution to restraints on the growth of the business, and a second case study of Small and Medium-sized Enterprise (SME) unable to articulate information system requirements was able to commission a sustainable system. Multi-view was used as a reflective framework, so practitioners were able to extract meaningful outcomes on both practice and praxis. Although the paper bases its speculations on a small number of examples the framework for reflection is offered as a model for future development and adoption elsewhere.